1995
DOI: 10.1002/chir.530070304
|View full text |Cite
|
Sign up to set email alerts
|

A new approach in exciton‐coupled circular dichroism (ECCD)—insertion of an auxiliary stereogenic center

Abstract: There are cases in which exciton coupling between two chromophores does not occur because the two electric transition moments which should interact are coplanar. This is seen with cyclohexane-1,4-diols (both ee or ea) and a wide variety of 3-hydroxy carotenoids, 3-hydroxyretinoids, etc. A general approach to deal with such cases is to acylate one of the hydroxyl groups with a chiral allenic acid substituted with a suitable chromophore, e.g., CHROM-CH = C = CH-COOH. The allenic bond introduces a 90 degrees twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 7 publications
3
48
0
Order By: Relevance
“…215 nm, of a sign predicted by application of the lactam octant rule [30,31], as indicated in Figure 3, and also similar to that seen in the CD spectrum of (R)-(-)-4-hydroxypiperidin-2-one [32]. Although more detailed studies are necessary to fully assign the CE's described to specific electronic transitions or exciton coupling effects [33,34], these observations provide a reference for chiroptical properties in similar systems.…”
Section: Cd-spectroscopymentioning
confidence: 86%
“…215 nm, of a sign predicted by application of the lactam octant rule [30,31], as indicated in Figure 3, and also similar to that seen in the CD spectrum of (R)-(-)-4-hydroxypiperidin-2-one [32]. Although more detailed studies are necessary to fully assign the CE's described to specific electronic transitions or exciton coupling effects [33,34], these observations provide a reference for chiroptical properties in similar systems.…”
Section: Cd-spectroscopymentioning
confidence: 86%
“…However, the CD spectrum of compound 2 showed an almost opposite Cotton effect to that of compound 1 . The CD spectra of compounds 1 and 2 confirmed that these two compounds were diastereomers [22,23]. …”
Section: Resultsmentioning
confidence: 84%
“…From these results, the max at 20°C is attributed to the S-chiral (lefthanded) H-aggregates of the hemicyanine moieties, according to the exciton chirality theory. 7 At the same time, these results indicate that the peptide lipid self-assembles at this concentration (0.1 mM); that is, this concentration is above the critical aggregation concentration of the peptide lipid. Conversely, in a good solvent, ethanol, the hemicyanine moieties did not form Haggregates and had a max at 484 nm ( Figure S7a).…”
Section: ¹1mentioning
confidence: 71%